Rechtsgeschichte als Geschichte von Normativitätswissen? - Thomas Duve (Rechtsgeschichte - Legal History)
The article proposes that legal history can fruitfully be understood as the history of the production of normative knowledge. Such a perspective builds on a long tradition of legal historical research on the formation of norms, ideas, doctrines and institutions. For the last two centuries, however, the main focus of legal historical research, especially in the German tradition, was directed towards what has been called »the law of jurists« (Juristenrecht). Legal historians were interested, ﬁrst and foremost, in the formation of the modern Western legal system as a product of the work of jurists. The production of normative knowledge by other epistemic communities and communities of practice received far less attention, nor did legal historians integrate praxeological aspects into their research. Looking at legal history as a continuous process of the translation – and thus the production – of normative knowledge can provide an analytical framework that helps overcome these constraints. It offers the possibility of integrating different epistemic communities and communities of practice into its analysis and is able to incorporate the study of practices, materiality and other longneglected aspects of norm production. Not least, it serves as a method for a truly global legal history. The results of such a legal history might be less suggestive and fascinating than the big legal historical narratives of rationalization, professionalization and the formation of Western law that have inspired legal historians from the northern hemisphere during the 20th century. It can, however, offer a more complex picture of the past and provides us with the intellectual tools for a better understanding of norm production in the 21st century.